Eytan The Development of a Precociously Gifted Child Artist - Golomb, Claire ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
The paper examines the early development of a highly talented child artist in light of three theories of graphic development in children: (1) drawing development is a search for increasingly satisfying solutions to graphic problems that proceeds along a stage-like path; (2) gifted children aspiring to be artists carefully imitate their culture's representational conventions; and (3) styles or projective systems are derived from natural perspective and are alternative ways of representation that are not ordered along a developmental dimension. Detailed analysis of the drawings of the child artist from the ages of 2 through 6 lead to the conclusion that even a precociously gifted child artist does not really skip stages or phases in his graphic development. The idea that drawings employ an arbitrary system of convention-based graphic symbols was not supported. The existence of an intrinsic logic that guides the child's motivated invention of drawing systems was supported. The drawings are attached. (14 references.) (DB)
ERIC Note: Paper presented at the Annual Convention of the American Psychological Association (98th, Boston, MA, August 10-14, 1990).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Art; Artists; Case Studies; Child Development; Creative Development; Developmental Stages; Freehand Drawing; Gifted; Individual Development; Preschool Children; Talent; Talent Development; Theories; Speeches/Meeting Papers; Reports, Research